The Sad Side of Happy Pills: A Case Study on Psychiatric Medication Across a Woman’s Lifespan? - Tochkov, Karin; Williams, Nichole (Advances in Social Sciences Research Journal, 2023)
The use of antidepressants can have many benefits and many consequences (American Psychiatric Association, 2010). 12.7% of Americans aged 12 and older reported taking an antidepressant in the previous month when surveyed between 2011 and 2014 (Pratt, Brody, & Gu, 2017). The purpose of this case study is to explore the impact these medications have on a person by exploring their role in the life of one woman, Jane Doe and to urge caution in prescribing practices.